Clinical application of respiratory elastance (CARE trial) for mechanically ventilated respiratory failure patients: a model-based study - Chiew, Yeong Shiong; Chase, J. Geoffrey; Arunachalam, Ganesaramachandran; Tan, Chee Pin; Loo, Nienloong; Chiew, Yeongwoei; Md Ralib, Azrina; Mat Nor, Mohd Basri (IFAC Secretariat, 2018)
Mechanical ventilation (MV) is the primary support for respiratory failure patients. MV treatment is difficult to manage due to the variable patient-specific disease state and response to MV treatment. Model-based methods have shown potential in providing unique, personalised information on patient condition for clinicians to guide MV treatment. This study presents a clinical observational trial to investigate the respiratory mechanics and quality of patient ventilator asynchrony conducted in a South-East Asia hospital intensive care unit (ICU). Pilot trial results included 7 study patients. Patient-specific respiratory mechanics Ers and Rrs were median 32.30 cmH2O/l [Interquartile range (IQR): 24.53-43.48] and 7.62 cmH2Os/l [IQR: 4.85-10.34]. The Normalised Area Under the Curve of Time-Varying Elastance (AUC-Edrs) across patients were 27.50 cmH2O/l [IQR: 24.97-28.34]. Patient ventilator interaction is assessed using an asynchrony index (AI), where AI had a median value of 27.0% [(IQR): 21.0-52.7]. Patient-specific respiratory mechanics displayed intra- and inter- patient variability, suggesting patients are different and evolved over time, and thus their MV settings should be patient-specific and time-varying. Model-based methods thus offer unique insight into patient-specific respiratory mechanics and the resulting opportunity to personalize and optimise MV based on evolving patient-specific needs.